2020
DOI: 10.1111/1750-3841.15420
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric strategies for nondestructive and rapid assessment of nitrate content in harvested spinach using Vis‐NIR spectroscopy

Abstract: The overuse of nitrogenous fertilizers leads to an increase in the nitrate content of green leafy vegetables. Consumption of food with excess nitrate is not advisable because it results in human ailment. In this study, spinach leaves were harvested from plants grown under nine varying (0 to 400 kg/ha) nitrogenous fertilizer doses. A total of 261 samples were used to predict the nitrate content in spinach leaves using Vis-NIR (350 to 2,500 nm). The nitrate content was measured destructively using the ion-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The model was considered as excellent when the SE P was less than two times the standard error of laboratory (SE L ). The SE P values of the AA (0.311 mg/100 g F.W), TPC (0.028 mg GAE/g D.W.), and TFC (1.537 mg RE/g D.W.) were almost 1.5–2 times the SE L (AA = 0.18 mg/100 g F.W; TFC = 0.97 mg RE/g D.W; TPC = 0.02 mg GAE/g D.W.) which indicates the excellent performance of the developed PLSR models (Mahanti et al ., 2020). The statistical results obtained in the present study for AA ( R 2 = 0.762; RPD = 2.059) estimation were better than the results reported in the previous studies for spinach ( R 2 = 0.33; RPD = 1.21) (Pérez‐Marín et al ., 2019), acerola ( R 2 = 0.65) (Malegori et al ., 2017), and citrus fruits ( R 2 = 0.77–0.87) (Santos et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The model was considered as excellent when the SE P was less than two times the standard error of laboratory (SE L ). The SE P values of the AA (0.311 mg/100 g F.W), TPC (0.028 mg GAE/g D.W.), and TFC (1.537 mg RE/g D.W.) were almost 1.5–2 times the SE L (AA = 0.18 mg/100 g F.W; TFC = 0.97 mg RE/g D.W; TPC = 0.02 mg GAE/g D.W.) which indicates the excellent performance of the developed PLSR models (Mahanti et al ., 2020). The statistical results obtained in the present study for AA ( R 2 = 0.762; RPD = 2.059) estimation were better than the results reported in the previous studies for spinach ( R 2 = 0.33; RPD = 1.21) (Pérez‐Marín et al ., 2019), acerola ( R 2 = 0.65) (Malegori et al ., 2017), and citrus fruits ( R 2 = 0.77–0.87) (Santos et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The model constructed using the full spectrum indicates that SNV is superior to MSC, SG, SG-SNV, and SG-MSC for identifying the starch content of potato slices quickly. Although suitable values of R c (0.9020), RMSEC (2.06), R p (0.9069), RMSEP (2.06), and RPD (2.33) were obtained, the full spectrum model is unsuitable for practical application due to the time-consuming and laborious modeling process; 42 therefore, the characteristic wavelength model was established. We found that under the same pretreatment conditions, the model based on the characteristic wavelength exhibited superior performance to the model based on the full spectrum, which indicates that developing a model based on the characteristic wavelength is ideal.…”
Section: Resultsmentioning
confidence: 99%
“…To eliminate the noise and highlight the useful information in the spectral data, different preprocessings of the raw spectrum has been studied, such as SG smoothing, multivariate scattering correction (MSC), first derivative, etc. ( Mahanti et al., 2020 ; Zhang et al., 2023 ). In this study, the raw spectra were preprocessed with continuous wavelet transform (CWT), which has great potential for extracting spectral information of CFPGE parameters.…”
Section: Methodsmentioning
confidence: 99%